Analysis of the Influence of Education and Regional Minimum Wage Value on Employment Opportunities and Economic Growth of the District/City of Bali Province 2011-2022 - Dewa Ayu Putri Wiadnyani; Made Twin Sri Budhi (International Journal of Management Research and Economics, 2024)
Low levels of education and minimum wages make job opportunities even lower, thus having an impact on economic growth. Various efforts are designed and implemented by the regional government which are solely used to increase growth for the region itself and are then expected to have a positive impact on the welfare of the community, however, there is still inequality in community welfare between districts/cities in Bali Province. The objectives of this research are 1) to analyze the influence of education level and minimum wage on employment opportunities in Bali Province, 2) to analyze the influence of education level, minimum wage and employment opportunities on economic growth in Bali Province, 3) To analyze how the influence of employment opportunities mediates education level and minimum wage on economic growth in Bali Province. The analysis techniques used in this research are descriptive analysis and path analysis. The data used is panel data consisting of a combination of time series and cross section data with 120 observations obtained through secondary data. The results of this research show that 1) the level of education has a positive and significant effect on job opportunities in Bali Province, 2) the minimum wage has a positive and significant effect on job opportunities in Bali Province, 3) the level of education has a positive and significant effect on economic growth in the Province Bali, 4) the minimum wage has a positive and significant effect on the economic growth of Bali Province, 5) employment opportunities as an intervening variable or mediate the level of education and the minimum wage on employment opportunities in the Province of Bali.